Molecular Structure and Regulation of P2X Receptors With a Special Emphasis on the Role of P2X2 in the Auditory System. Issue 8 (30th December 2015) - Mittal, Rahul; Chan, Brandon; Grati, M'hamed; Mittal, Jeenu; Patel, Kunal; Debs, Luca H.; Patel, Amit P.; Yan, Denise; Chapagain, Prem; Liu, Xue Zhong
Abstract : The P2X purinergic receptors are cation‐selective channels gated by extracellular adenosine 5′‐triphosphate (ATP). These purinergic receptors are found in virtually all mammalian cell types and facilitate a number of important physiological processes. Within the past few years, the characterization of crystal structures of the zebrafish P2X4 receptor in its closed and open states has provided critical insights into the mechanisms of ligand binding and channel activation. Understanding of this gating mechanism has facilitated to design and interpret new modeling and structure–function experiments to better elucidate how different agonists and antagonists can affect the receptor with differing levels of potency. This review summarizes the current knowledge on the structure, activation, allosteric modulators, function, and location of the different P2X receptors. Moreover, an emphasis on the P2X2 receptors has been placed in respect to its role in the auditory system. In particular, the discovery of three missense mutations in P2X2 receptors could become important areas of study in the field of gene therapy to treat progressive and noise‐induced hearing loss. J. Cell. Physiol. 231: 1656–1670, 2016. © 2015 Wiley Periodicals, Inc. Abstract : In this review article, we discussed the current knowledge on the structure, activation, allosteric modulators, function, and location of the different P2X receptors. Moreover, an emphasis on the P2X2 receptors has been placed in respect to its role in the auditory system.